2006
DOI: 10.2208/prohe.50.613
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Flood Risk Assessment of Global Warming by Regional Climate Model

Abstract: 正会員 博(工) 国土技術政策総合研究所 流域管理研究官(〒305-0804 茨城県つくば市旭一番地)2 工修 国土技術政策総合研究所 河川研究部(〒305-0804 茨城県つくば市旭一番地) 3 正会員 政策修 国土技術政策総合研究所 河川研究部(〒305-0804 茨城県つくば市旭一番地)The influence of global warming on hazard risk is estimated from the results of the regional climate model by Japan Meteorological Agency and Meteorological Research Institute. The horizontal resolution of the model is about 20km and the model outputs are expected to be useful for the risk assessment of the future. Before beginning the risk assessment, the model out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Wada et al (2006) found that it was necessary that the assessment of probable precipitation using MRI-RCM20 be based on values averaged over a region of about 60 kilometers square in extent. In contrast, Wada et al (2008) showed that it was possible to assess the reproducibility of the probable precipitation at individual grid points with MRI-GCM20.…”
Section: Introductionmentioning
confidence: 99%
“…Wada et al (2006) found that it was necessary that the assessment of probable precipitation using MRI-RCM20 be based on values averaged over a region of about 60 kilometers square in extent. In contrast, Wada et al (2008) showed that it was possible to assess the reproducibility of the probable precipitation at individual grid points with MRI-GCM20.…”
Section: Introductionmentioning
confidence: 99%